Pengaruh Motivasi dan Kepuasan Kerja Terhadap Peningkatan Kinerja Karyawan CV. Sabrina Usaha Mandiri Jakarta Utara - Muharram, Ari; Fitriani, Risma; Momon, Ade (JURMATIS (Jurnal Manajemen Teknologi dan Teknik Industri), 2023)
The problem of motivation and satisfaction at CV Sabrina Usaha Mandiri needs to be overcome through improving employee performance with training, support and rewards. This study is to determine the model of the corrected hypothesis from that perspective. It is hoped that the results of the research can help companies improve employee performance. Quantitative-associative design to test the hypothesis of the relationship between motivation, job satisfaction, and employee performance in CV. Sabrina Independent Business. A population of 24 employees, using google form instruments and processed with IBM SPSS 23. Validation and reliability are performed by partial testing procedures and simultaneous tests to produce corrected models. This study shows the results that employee motivation has a positive and significant correlation and reliability to improve the performance of street light installation projects in the North Jakarta area. The results of partial and simultaneous tests on the corrected hypothesis model also showed that motivation and job satisfaction had an effect on improving performance on the project. Therefore, it is important for project management to pay attention to and maintain the motivation and job satisfaction of the workers in the project in order to achieve optimal results. Motivation and job satisfaction can play a role in improving the performance of street light installation projects in the North Jakarta area by paying attention to the quality of motivation and job satisfaction of the employees involved